State‐of‐the‐art in smart streetlight systems: a review. Issue 1 (10th January 2020) - Mahoor, Mohsen; Hosseini, Zohreh S.; Khodaei, Amin; Paaso, Aleksi; Kushner, Daniel
Abstract : The utilisation of smart streetlights is gaining more attention in urban planning, as it potentially reduces streetlights' operation and maintenance costs, offers additional benefits in terms of safety, security, efficiency, versatility, and scalability, and sets the stage for further smart city applications. This study provides an extensive overview of state‐of‐the‐art research on smart streetlights from various perspectives, including smart city applications, communications, control strategies, and cybersecurity, with the objective of laying down a foundation for future improvements of smart streetlight systems as well as establishing a basis for comparing existing technologies.